PENGARUH LATIHAN SIDE HOP TERHADAP POWER OTOT ATLET PENCAK SILAT REMAJA PUTRA OKIDO PEKANBARU - Kartika Kartika; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The problem in this study is that a power deficiency in leg muscle, it is seen from the results of various observations during the 6 times exercise meeting and at the time of the match and this is one of the factors that cause the defeat. This type of research is a experiment to see the effect of the form of exercise. The purpose of this study was to determine the effect of side hop exercise to muscle power of the limbs on the youth boy pencak silat team okido pekanbaru.The population in this study were the 4 athletes of youth boy pencak silat okido pekanbaru. Sampling technique i.e. by using total sampling, where the number of the overall population sampled. Techniques of data retrieval get of preetest and posttest. The instrument in this study is use the standing board jump as a tool to measure leg muscle power. The analysis is conducted by using t-test. Based on the analysis of data and discussion, it can be concluded that there is significant influence of side hop exercise to the leg muscle power of athletes pencak silat the of the youth boy athletes of pekanbary okido proven with Tcount amounted to 14.48 and Ttable 2,353. That Tcount > Ttable. Economic consequences of the å=0.05Keywords: Side Hops Exercise, Leg Muscle Power